-5(4p+3)-37=4(3p+3)

Simple and best practice solution for -5(4p+3)-37=4(3p+3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5(4p+3)-37=4(3p+3) equation:


Simplifying
-5(4p + 3) + -37 = 4(3p + 3)

Reorder the terms:
-5(3 + 4p) + -37 = 4(3p + 3)
(3 * -5 + 4p * -5) + -37 = 4(3p + 3)
(-15 + -20p) + -37 = 4(3p + 3)

Reorder the terms:
-15 + -37 + -20p = 4(3p + 3)

Combine like terms: -15 + -37 = -52
-52 + -20p = 4(3p + 3)

Reorder the terms:
-52 + -20p = 4(3 + 3p)
-52 + -20p = (3 * 4 + 3p * 4)
-52 + -20p = (12 + 12p)

Solving
-52 + -20p = 12 + 12p

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '-12p' to each side of the equation.
-52 + -20p + -12p = 12 + 12p + -12p

Combine like terms: -20p + -12p = -32p
-52 + -32p = 12 + 12p + -12p

Combine like terms: 12p + -12p = 0
-52 + -32p = 12 + 0
-52 + -32p = 12

Add '52' to each side of the equation.
-52 + 52 + -32p = 12 + 52

Combine like terms: -52 + 52 = 0
0 + -32p = 12 + 52
-32p = 12 + 52

Combine like terms: 12 + 52 = 64
-32p = 64

Divide each side by '-32'.
p = -2

Simplifying
p = -2

See similar equations:

| 10y=6y+8 | | 4x^3+4x^2+16x=0 | | 5x-3=-9 | | 18x=54.198 | | 7(c-5)=8(c-6) | | Y-17=11 | | 9=x(9-x) | | -15+8x=8x-8 | | .25x-6=12 | | 9-(2+3)=2(6-2) | | 6+-5n+2n=33+-96 | | 100=25-7.5d | | 3(x+4)+2x=4x+14 | | 2.5x-6=12 | | C+2=3c+9 | | 8.08=-11402x^2+766.68x-6.6669 | | -81x^2+4=0 | | W-9c=8forw | | 3=4(5+6n) | | 6-5n+2n=3-96 | | X^2-5x=864 | | 1.33x-5=7 | | 2a-6+5=2a | | 100+.05x=200 | | y=80x+4 | | 4x-(10x-x)=7.5 | | 0=3x^2+13x+12 | | 32=6p-10 | | -5y+1(-2y-5)=7-8(1-y) | | 18x-30=15x+12 | | 8f+19=19 | | 1+1+1+1+1+1+1+1+1+1+1+1*0+2= |

Equations solver categories